CAUSES AND CONSEQUENCES OF BURNOUT SYNDROME IN NURSING PROFESSIONALS: LITERATURE REVIEW - Moreira, Luciana brito (2018)
The objective of the study was to identify the causes and consequences of Burnout Syndrome in nursing professionals. This is an integrative review of literature with search in databases: (LILACS) Latin American and Caribbean Literature in Health Sciences, (SCIELO) Scientific Electronic Library Online, Google academic, (MEDLINE) Medical Literature Analysis and Retrieval System Online, (BIRENE) Latin American and Caribbean Center on Health Sciences Information, 9 articles were selected according to the inclusion and exclusion criteria. Burnout Syndrome has its definition as chronic stress, causing nursing professionals in the field of work numerous emotional factors. Its consequences are physical and psychic predisposition, altering the quality of life of the professional of the nursing team. In the treatment of Burnout Syndrome it is necessary that they are approached as collective and organizational problems, and appropriate measures are applied for an effective assistance.